Solution Focused Brief Counseling Teknik Thought Stoping Untuk Mengatasi Kecamasan Diri Terhadap Isu Virus Corona-19 - Teuku Fadhli; Ilham Khairi Siregar (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2020)
Anxiety is a behaviour formed by the subconscious that then arises due to environmental pressures that affect unproductive behavior. This research method experiment in the form of research draft Non Equivalent Group Pretest-Postest Control Group. Subject control research is selected through a random sampling mechanism. Researchers placed each group totalling eight students in experimental groups and control groups. The experiment group will be given special intervention through the counseling Stoping technique group with the Solution Focused Brief approach. Data collection techniques with self-anxiety instruments (Skla Likert) that have been conducted expert validation tests and then tested for instruments. From the results of the study showed that the SFBC approach with TS engineering researchers effectively to encourage self-anxiety, the researchers further advise that subsequent researchers so that these techniques and approaches can be used in emergency conditions in both public and school environments with regard to the scientific conventions.